KNOWLEDGE, AWARENESS, AND PREVALENCE OF ANDROPHOBIA AMONG UNDERGRADUATE DENTAL STUDENTS - A QUESTIONNAIRE SURVEY - S. Bhavesh, Dhanraj Ganapathy, L. Keerthi Sasanka, (Drugs and Cell Therapies in Hematology, 2022)
Introduction: Phobia is known as an extreme or irrational fear of or aversion to something. Androphobia is defined as a fear of men. The term originated inside feminist movements to balance the term ‘gynophobia’ which is fear of women. Both men and women can be affected by Androphobia Aim: The main aim of the study is to conduct a survey to assess the awareness and prevalence of Androphobia among dental students. Materials and methods: The present study was a cross sectional study conducted among 100 dental students. An online e-questionnaire was prepared with questions to explore the awareness regarding androphobia and the responses were collected and statistically analysed in SPSS, the statistical analysis was done using descriptive statistics. Results: Only 52% of the dental students know what Androphobia is. Most of the responses recorded do not fear men, only 40% fear for men. Among symptoms observed by the populations, increased heart beat is 74.4%, which is more among the dental students. Around 58.4% of the dental students did not have any impact on their life because of Androphobia.39% of the students talk frequently to men and 30% of the students often talk to men. Out of total responses, 55.3% have not taken any steps to overcome Androphobia, only 19.1% have taken steps to overcome Androphobia. Conclusion: In this present study, the observed results had negative responses, which states that most of the population did not have fear of men and most of them have not taken any steps to overcome Androphobia.